2015
DOI: 10.1074/jbc.m114.593871
|View full text |Cite
|
Sign up to set email alerts
|

Interferon-stimulated Gene 15 (ISG15) and ISG15-linked Proteins Can Associate with Members of the Selective Autophagic Process, Histone Deacetylase 6 (HDAC6) and SQSTM1/p62

Abstract: Background: ISG15 is a Ub-like protein that conjugates cellular and pathogenic proteins during the innate immune response. Results: ISG15 associates with the selective autophagic factors HDAC6 and p62, leading to degradation of ISG15 conjugates. Conclusion:The IFN response leads to ISG15 expression allowing for its association with HDAC and p62. This may mark proteins for autophagy. Significance: This finding provides evidence of an interferon-stimulated pathway linked to autophagy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
82
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(88 citation statements)
references
References 42 publications
(47 reference statements)
2
82
0
1
Order By: Relevance
“…We therefore hypothesized that antiviral effectors directly modulate the autophagic machinery. In cancer cell lines, the ubiquitin-like molecule ISG15 (76) modifies beclin 1 (77) and can bind directly to p62 (78). We found that ISG15 colocalized with Ͼ70% of clusters (Fig.…”
Section: Hsv-1 Replication In Tg Neurons Induces Atypical Autophagic mentioning
confidence: 81%
See 1 more Smart Citation
“…We therefore hypothesized that antiviral effectors directly modulate the autophagic machinery. In cancer cell lines, the ubiquitin-like molecule ISG15 (76) modifies beclin 1 (77) and can bind directly to p62 (78). We found that ISG15 colocalized with Ͼ70% of clusters (Fig.…”
Section: Hsv-1 Replication In Tg Neurons Induces Atypical Autophagic mentioning
confidence: 81%
“…Another line of investigation in our lab is driven by the fact that p62 self-oligomerizes, possibly promoting cluster formation (87). Alternatively, vesicle clustering may be promoted by innate mediator ISG15 (28,88,89) which decorates the clusters and is known to interact with beclin 1 and p62 (77,78).…”
Section: Discussionmentioning
confidence: 99%
“…FAT10 has been shown to bind to and regulate the solubility of polyQ proteins, and localize to aggresomes upon proteasome inhibition [58,59]. ISG15 has recently been shown to bind to HDAC6 and p62, and to promote degradation of aggregated proteins via aggrephagy [60].…”
Section: Aggrephagymentioning
confidence: 99%
“…Besides Ub-based selective autophagy, HDAC6 is associated with autophagic clearance of IFN-induced ISG15-conjugated proteins. HDAC6 and p62 independently bind ISG15 and facilitate the autophagosome/lysosome degradation of ISG15 conjugates (Nakashima et al 2015). The role of HDAC6 in the fusion event is to control acetylation of salt-inducible kinase 2 (SIK2).…”
Section: Possible Mechanisms Of Hdacs In Cancer Developmentmentioning
confidence: 99%